24-Hour Ultramarathon and the Status of Thyroid Hormones: Case Report - Bubnjević, Ksenija; Grujičić, Dragan; Romanov, Romana; Miletić, Vladimir; Glavač, Boris (International Journal of Innovative Research in Medical Science, 2023)
Introduction: Thyroid hormones play a very significant role in metabolism, so any impairment of their levels may bring about a chronic disease of the thyroid gland. A question asked is whether continuous long-distance running can affect changes in TSH and T4 values in a person with Hypothyroidism. This Case report aims to explore the influence of high-intensity running (confirmed by the control of the CK) on the status of thyroid hormones. Case report: The female subject in this case report in an ultramarathon runner (40 years old) who has a diagnosis of the Hashimoto tyroiditis. From October to June 2022, she trained for the competition in running for 24 hours. To determine the status of thyroid hormones, some biochemical measurements of urine and blood were performed immediately before and after the race (competition). The imbalance of TSH hormone values was identified a day before (5.390U/ml) and a day after (5.700 U/ml) the race, while blood parameters increased after the race for AST (148 U/L), CK (2265 U/L) and CRP (7.51 mg/L). Conclusion: Analysis of the results of this case report showed that there were no significant changes in the TSH hormone after running for 24 hours.